The effects of chromatin organization on variation in mutation rates in the genome - Makova, Kateryna D. (Nat Rev Genet, 2015)
The variation in local rates of mutations can affect both the evolution of genes and their function in normal and cancer cells. Deciphering the molecular determinants of this variation will be aided by resolving distinct types of mutation, since they differ in regional preferences and in associations with genomic features. Chromatin organization contributes to regional variation in mutation rate, but differently among mutation types. In both germ-line mutations and somatic mutations, base substitutions are more abundant in regions of closed chromatin, perhaps reflecting error accumulation late in replication. In contrast, a distinctive mutational state with very high levels of indels and substitutions is enriched in regions of open chromatin. These associations illuminate an intricate interplay between the nucleotide sequence of DNA and its dynamic packaging into c inhromatin, and they have important implications for current biomedical research. This review focuses on the recent studies showing associations between chromatin state and mutation rates, including pairwise and multivariate investigations of germ-line and somatic (particularly cancer) mutations.